Preparation method and application of copper-based catalyst coated with quaternary ammonium cation cross-linked copolymer
Coating copper-based catalysts by quaternary ammonium cationic crosslinked copolymers is solved, and the oxidation corrosion and proton competition problems of copper-based catalysts under acidic conditions are improved, and the selectivity and stability of CO2 reduction to produce C2+ products is simplified, and the preparation process is reduced and the cost is reduced.
Patent Information
- Application Number
- CN202510365058.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-07-11
AI Technical Summary
Under acidic conditions, copper-based catalysts are prone to oxidation or corrosion, resulting in loss of active sites, reducing catalyst activity and selectivity, and high proton concentrations can easily lead to hydrogen generation competing for electrons with CO2 reduction reaction, reducing the efficiency and selectivity of CO2 reduction to produce C2+ products.
Quaternary ammonium cationic crosslinked copolymer is used to coat the copper-based catalyst, stabilize the intermediate through electrostatic action, adjust the electronic structure and wettability of the catalyst surface, promote proton-coupled electron transfer, form specific adsorption, and increase the collision between CO2 molecules and carbon-based intermediates.
The selectivity and stability of the copper-based catalysts to produce C2+ products under acidic conditions are improved, the reaction rate and catalytic performance are significantly improved, the catalyst life is extended, and the production cost is reduced.
Smart Images

Figure CN120291149A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of carbon dioxide electroreduction catalysts, and particularly relates to the preparation of a quaternary ammonium cation cross-linked copolymer-coated copper-based catalyst (Cu-PHMAC) and its application in the electroreduction of CO2 to ethanol. Background Art
[0002] With the continuous acceleration of the global industrialization process, the amount of CO2 emitted by various human activities has shown a linear upward trend. The excessive emission of CO2 has caused a sharp change in the global climate pattern, seriously disrupting the original stable carbon cycle order among the ecosystem, the earth, the atmosphere, and water bodies, bringing an unprecedented crisis to human survival. Therefore, it is urgent to explore effective CO2 conversion strategies.
[0003] Among many CO2 conversion technologies, electrocatalysis has become one of the ideal paths to convert CO2 into high-value chemicals due to its significant advantages such as easy control of reaction conditions, wide sources of raw materials and low cost, clean and sustainable energy, etc., and is expected to reshape the balance of the carbon cycle. However, the current electrocatalytic CO2 reduction process still faces many problems. On the one hand, the hydrogen evolution side reaction occurs frequently, which not only consumes a large amount of electric energy but also reduces the production efficiency of the target product; on the other hand, under alkaline conditions, CO2 is prone to react with OH - to form carbonate precipitates, which may deposit on the electrode or membrane surface, covering the electrode active sites, reducing the effective area of the electrode, hindering the transport and reaction of CO2, resulting in a decrease in CO2 utilization rate, and at the same time, it will also affect the performance and stability of the catalyst. In contrast, due to the higher solubility of CO2 in acidic conditions and the faster proton transfer rate, catalytic reduction of CO2 in acidic conditions can avoid the problem of carbonate formation in alkaline systems to a certain extent, which helps to further improve the reaction rate and the Faraday efficiency of the product in the electrocatalytic reduction of CO2.
[0004] As an important clean energy carrier and basic chemical raw material, ethanol has irreplaceable application value in fields such as fuel additives, organic synthesis, and medicine and health. Traditional ethanol production mainly relies on biomass fermentation technology, but this process has problems such as seasonal limitation of raw material supply, high energy consumption, and large carbon emissions. Using electrocatalytic carbon dioxide reduction technology to convert the greenhouse gas CO2 into high-value ethanol can not only realize the recycling of carbon resources but also provide a new path for renewable energy storage.
[0005] In the field of electrocatalytic reduction of CO2, the production of products containing two or more carbon atoms (C 2+ ) (such as ethylene, ethanol, etc.) has attracted much attention due to the high added value of the products. However, the CO2 molecule has strong chemical inertness, and its reduction to C 2+The product needs to undergo multiple proton-electron coupling reactions, involving complex processes such as C-C coupling and regulation of the adsorption energy of intermediates, which have extremely high requirements for the geometric configuration and electronic structure of the catalyst active sites. Copper-based catalysts, due to their unique catalytic properties, are currently the only metal materials that can efficiently catalyze the formation of multi-carbon products from CO2. However, in an acidic system, on the one hand, acidic conditions are likely to cause surface oxidation or corrosion of copper-based catalysts, resulting in the loss of active sites, thereby reducing the activity and selectivity of the catalyst and shortening the service life of the catalyst; on the other hand, under acidic conditions, the concentration of protons is relatively high, and the kinetics of the hydrogen evolution reaction are more favorable, that is, hydrogen ions (H + ) are more likely to obtain electrons to generate hydrogen gas (H2), which will compete with the CO2 reduction reaction for electrons and active sites on the catalyst surface, resulting in a reduction in the electrons used for CO2 reduction to generate C 2+ products, thereby reducing the selectivity and efficiency of CO2 reduction to generate C 2+ products. Therefore, developing a new type of catalyst to improve the efficiency and stability of copper-based catalysts for electrocatalytic reduction of CO2 to generate C 2+ products is an issue that needs to be solved currently. Summary of the Invention
[0006] To address the above problems, the object of the present invention is to provide a copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer, a preparation method thereof, and its application in electrocatalytic CO2 reduction. By using cations to regulate the electronic structure of the catalyst active center and the wettability of the catalyst, proton-coupled electron transfer is promoted, and the interfacial microenvironment is regulated. The key intermediates are stabilized through electrostatic interactions, reducing the formation energy barrier. The adsorption of Cu and the active intermediates changes from surface linear adsorption to specific adsorption, which helps to enrich CO2 molecules and carbon-based intermediates near the Cu catalytic sites, increasing the effective collisions between molecules, thereby accelerating the reaction rate and enhancing the selectivity of producing multi-carbon products from carbon dioxide reduction. The preparation method of the copper-based catalyst coated with the quaternary ammonium cation cross-linked copolymer of the present invention is simple, mild, and low-cost, and has high selectivity in electrocatalytic reduction of CO2, with high stability and application value.
[0007] To achieve the above object, the present invention first provides a preparation method of a copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer, comprising the following steps:
[0008] (1) Dissolve methyl methacrylate, a cross-linking agent, and an initiator in methanol under an inert atmosphere to obtain a reaction mixture;
[0009] (2) Dissolve a cationic polymerizable monomer in water, and add the reaction mixture obtained in step (1) to the solution. Heat and stir the mixture under inert gas protection. After extraction, precipitation, washing, and drying of the mixed solution, a quaternary ammonium cation cross-linked copolymer (PHMAC) is obtained;
[0010] (3) Mix the copper powder and the quaternary ammonium cation cross-linked copolymer obtained in step (2) evenly to obtain a mixture, and add a solvent to the mixture to dissolve it to obtain Cu-PHMAC.
[0011] In one embodiment of the present invention, the cross-linking agent in step (1) includes any one of acrylamide, methacrylamide, N-methylacrylamide, N-isopropylmethylacrylamide, N,N-dimethylmethylacrylamide, N,N-diethylmethylacrylamide, N-methyl-N-ethylmethylacrylamide, N-hydroxyethylmethylacrylamide, N-(hydroxymethyl)acrylamide, and dopamine methacrylamide.
[0012] In one embodiment of the present invention, the cationic polymerizable monomer in step (2) includes any one of methacryloyloxyethyltrimethylammonium chloride, acryloyloxyethyltrimethylammonium chloride, acrylamidopropyltrimethylammonium chloride, diallyldimethylammonium chloride, and [3-(methacrylamido)propyl]trimethylammonium chloride.
[0013] In one embodiment of the present invention, the molar ratio of the cross-linking agent, methyl methacrylate, and the cationic polymerizable monomer is 1 to 1.3:2:1 to 2.
[0014] In one embodiment of the present invention, the initiator in step (1) includes at least one of 2,2'-azobis(2-methylpropionitrile), azobisisobutyronitrile, dimethyl 2,2'-azobis(2-methylpropionate), and azodicyanovaleric acid.
[0015] In one embodiment of the present invention, the molar ratio of the initiator and the cross-linking agent in step (1) is 10 to 20:1, preferably 10 to 14:1, and more preferably 10 to 12:1.
[0016] In one embodiment of the present invention, the molar volume ratio of methyl methacrylate to methanol in step (1) is 1 mmol:3 to 10 mL.
[0017] In one embodiment of the present invention, the inert atmosphere in step (1) is argon or nitrogen.
[0018] In one embodiment of the present invention, the volume ratio of the water in step (2) to the volume of methanol in step (1) is 3 to 4:6 to 7.
[0019] In one embodiment of the present invention, in step (2), before adding the reaction mixture, the aqueous solution of the cationic polymerizable monomer is first purified, and the solvents used for purification include at least one of ethyl acetate, cold ether, and dichloromethane.
[0020] In one embodiment of the present invention, the volume ratio of the solvent used for purification to the volume of the aqueous solution of the cationic polymerizable monomer is 1:2 to 3.
[0021] In one embodiment of the present invention, the inert gas in step (2) is argon or nitrogen, preferably argon, the heating temperature is 70 - 80 °C, and the stirring time is 36 - 48 h.
[0022] In one embodiment of the present invention, the extraction and precipitation in step (2) are carried out by using an organic solvent to extract and precipitate the mixed solution, and the organic solvent includes at least one of cold ethyl ether, dichloromethane, and ethyl acetate.
[0023] In one embodiment of the present invention, for the extraction and precipitation in step (2), it is first extracted and precipitated with cold ethyl ether, and then extracted and precipitated twice with dichloromethane.
[0024] In one embodiment of the present invention, the drying in step (2) is carried out in a vacuum oven at 50 - 70 °C for 10 - 12 h.
[0025] In one embodiment of the present invention, in step (3), the mass ratio of the copper powder to the quaternary ammonium cation cross-linked copolymer is 3 - 5:1.
[0026] In one embodiment of the present invention, in step (3), the solvent is at least one of dichloromethane, methanol, and ethyl acetate.
[0027] In one embodiment of the present invention, in step (3), the mass-volume ratio of the mixture to the solvent is 5 - 6 mg:1 mL.
[0028] The present invention provides a copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer prepared according to the above method.
[0029] The present invention also provides an application of the copper-based catalyst coated with the above quaternary ammonium cation cross-linked copolymer in the fields of environmental protection, catalysis, and green energy.
[0030] In one embodiment of the present invention, the application in the catalytic field includes applying the copper-based catalyst coated with the above quaternary ammonium cation cross-linked copolymer to the electrocatalytic reduction of CO2.
[0031] In one embodiment of the present invention, the electrocatalytic reduction of CO2 includes the following steps: using a carbon paper loaded with the copper-based catalyst coated with the quaternary ammonium cation cross-linked copolymer as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, and carrying out the reduction of electrocatalytic CO2 in a flow cell device of a three-electrode system.
[0032] In one embodiment of the present invention, the loading amount of the quaternary ammonium cation cross-linked copolymer-coated copper-based catalyst on the carbon paper is 1-2 mg cm -2 .
[0033] In one embodiment of the present invention, the cathode electrolyte used in the cathode chamber of the flow cell includes at least one of sulfuric acid, potassium sulfate, and potassium chloride, and the cathode electrolyte preferably includes sulfuric acid and potassium sulfate.
[0034] In one embodiment of the present invention, the concentration of the cathode electrolyte is a mixed solution of 0.1 mol / L sulfuric acid and 0.25 mol / L potassium sulfate.
[0035] In one embodiment of the present invention, the anode electrolyte used in the anode chamber of the flow cell includes at least one of sulfuric acid, potassium sulfate, and potassium chloride, the anode electrolyte preferably includes sulfuric acid and potassium sulfate, and the cathode chamber and the anode chamber are separated by a proton exchange membrane.
[0036] In one embodiment of the present invention, the concentration of the anode electrolyte is a mixed solution of 0.1 mol / L sulfuric acid and 0.25 mol / L potassium sulfate.
[0037] In one embodiment of the present invention, the electrocatalytic CO2 reduction reaction is carried out at atmospheric pressure in a constant current mode, and the current range is 50-500 milliamperes per square centimeter.
[0038] Advantages of the present invention:
[0039] (1) In the present invention, a quaternary ammonium cation cross-linked copolymer-coated copper-based catalyst is successfully prepared by adding a cationic polymerizable monomer, methyl methacrylate, and a cross-linking agent to an initiator to polymerize into a quaternary ammonium cation cross-linked copolymer PHMAC, and then mixing PHMAC with copper powder. The introduction of the quaternary ammonium cation cross-linked copolymer optimizes the distribution of active sites of the copper-based catalyst, simplifies the traditional complex preparation process, significantly reduces the production cost. At the same time, the impedance of the catalyst material is small, which will help to improve the reaction rate of the electrocatalytic carbon dioxide reduction reaction.
[0040] (2) The present invention uses a specific catalyst coating method, mixing and grinding PHMAC with copper powder so that PHMAC is coated on the surface of copper particles to form a catalyst layer. The distribution of PHMAC on the catalyst layer can be controlled during the reaction process, which helps to improve the stability of the catalyst. By coating and protecting the copper-based surface with PHMAC, the oxidation corrosion of the copper-based material under acidic conditions can be reduced, and the service life of the catalyst is extended.
[0041] (3) The present invention utilizes the cationic properties of PHMAC to adjust the electronic structure and wettability of the copper-based catalyst surface, promote proton-coupled electron transfer, and inhibit the hydrogen evolution reaction (HER). By preferentially adsorbing *CO intermediates through the local electrostatic field, it breaks through the traditional high-concentration cation dependence and achieves highly selective electroreduction of carbon dioxide at a lower cation concentration and in an acidic electrolyte. At a current density of 250 mA / cm 2 , the Faradaic efficiency of C2 products reaches 72.5%, and the Faradaic efficiency of ethanol is 46.6%. Compared with the uncoated commercial copper powder (FE C2 only 37%), the catalytic performance is significantly improved.
[0042] (4) The Cu-PHMAC provided by the present invention can operate at a current density of 50-500 mA / cm² in a flow cell of a three-electrode system, indicating that the Cu-PHMAC prepared by the method of the present invention has good stability in electroreducing CO2 to C 2+ products. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is the XRD picture of the Cu-PHMAC prepared in Example 1.
[0044] Figure 2 is the infrared picture of the PHMAC material prepared in Example 1.
[0045] Figure 3 is the nuclear magnetic resonance carbon spectrum of the PHMAC material prepared in Example 1
[0046] Figure 4 is the measurement diagram of the electrochemically active area of the copper-based catalyst materials of Examples 1-2 and Comparative Example 1.
[0047] Figure 5 is the impedance diagram of the copper-based catalyst materials of Examples 1-2 and Comparative Example 1.
[0048] Figure 6 is the CO2ER performance diagram of the Cu-PHMAC Ⅰ prepared in Example 1.
[0049] Figure 7 is the CO2ER performance diagram of the Cu-PHMAC Ⅱ prepared in Example 2.
[0050] Figure 8 is the CO2ER performance diagram of the pure commercial copper powder material of Comparative Example 1.
[0051] Figure 9 is the CO2ER performance diagram of the Cu-PHMAC Ⅲ prepared in Comparative Example 2.
[0052] Figure 10 CO2ER performance graph of Cu-PHM prepared in Comparative Example 3. Detailed implementation manners
[0053] The following describes the preferred embodiments of the present invention. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0054] Example 1
[0055] A preparation method of a quaternary ammonium cation cross-linked copolymer-coated copper-based catalyst includes the following steps:
[0056] (1) Dissolve 2.00 mmol of N-(hydroxymethyl)acrylamide (HAM), 4.00 mmol of methyl methacrylate (MMA), and 0.20 mmol of 2,2′-azobis(2-methylpropionitrile) (AIBN) in 16.8 mL of anhydrous methanol in a 50 mL three-necked flask under an argon atmosphere to obtain a reaction mixture.
[0057] (2) Dissolve 2.00 mmol of [3-(methacrylamido)propyl]trimethylammonium chloride (MAPTAC) in 7.2 mL of deionized water, and then perform three organic extractions with ethyl acetate (3.6 mL) to purify the charged monomer [3-(methacrylamido)propyl]trimethylammonium chloride (MAPTAC) to obtain an aqueous phase. Then mix the aqueous phase with the reaction mixture obtained in step (1), and degas with argon at room temperature for 30 minutes. Under argon protection, stir the reaction solution at 70 °C for 48 hours to obtain a polymer solution. Precipitate the polymer solution with cold diethyl ether, and then reprecipitate the product twice in dichloromethane, and dry it under vacuum. The obtained white solid is PHMACⅠ.
[0058] (3) Weigh 15 mg of commercial copper powder (purity ≥ 99.9%) and premix it with 5 mg of PHMACⅠ obtained in step (2), then place it in a mortar and grind it carefully to mix evenly, so that the polymer uniformly coats the surface of the copper particles. Transfer the obtained composite powder to a three-necked flask, add 1 mL of dichloromethane solvent, and ultrasonically disperse the mixed solution. Finally, Cu-PHMACⅠ is obtained.
[0059] Perform XRD detection on the Cu-PHMACⅠ obtained in Example 1, and the results are as Figure 1 shown. XRD analysis shows that the crystal structure of copper is not changed during this treatment process, and the valence state of Cu in the reaction system remains unchanged. From Figure 2 it can be seen that Cu-PHMACⅠ shows an -NH- vibration peak at about 1500 cm -1 and an -OH- vibration peak at 1400 cm -1 and an -C=O- vibration peak at 1700 cm-1 The -OH- vibration peak appears at. Starting from Figure 3 It can be seen that absorption peaks of multiple organic functional groups appear in the NMR spectrum, corresponding to different carbon atoms of the target PHMAC respectively, indicating that Cu-PHMAC was successfully prepared by this experimental scheme.
[0060] Example 2
[0061] A preparation method of a copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer (PHMACⅡ) includes the following steps:
[0062] (1) Dissolve 2.00 mmol of N-(hydroxymethyl)acrylamide (HAM), 4.00 mmol of methyl methacrylate (MMA), and 0.20 mmol of 2,2′-azobis(2-methylpropionitrile) (AIBN) in 16.8 mL of anhydrous methanol in a 50 mL three-necked flask under an argon atmosphere to obtain a reaction mixture.
[0063] (2) Dissolve 3.00 mmol of [3-(methacryloylamino)propyl]trimethylammonium chloride (MAPTAC) in 7.2 mL of deionized water, and then perform three organic extractions with ethyl acetate (3.6 mL) to purify the charged monomer [3-(methacryloylamino)propyl]trimethylammonium chloride (MAPTAC) to obtain an aqueous phase. Then mix the aqueous phase with the reaction mixture obtained in step (1), and degas with argon at room temperature for 30 minutes. Under argon protection, stir the reaction solution at 70 °C for 48 hours to obtain a polymer solution. Precipitate the polymer solution with cold diethyl ether, and then reprecipitate the product twice in dichloromethane, and dry it under vacuum. The obtained white solid is PHMACⅡ.
[0064] (3) Weigh 15 mg of commercial copper powder (purity ≥ 99.9%) and premix it with 5 mg of PHMACⅡ obtained in step (2), then place it in a mortar and grind it carefully to mix evenly, so that the polymer uniformly coats the surface of the copper particles. Transfer the obtained composite powder to a three-necked flask, add 1 mL of dichloromethane solvent, and ultrasonically disperse the mixed solution. Finally, Cu-PHMACⅡ is obtained.
[0065] Comparative Example 1
[0066] Commercial copper powder was used as the catalyst in Comparative Example 1.
[0067] Figure 4 Measurement diagrams of the electrochemically active surface area of the catalysts of Examples 1-2 and Comparative Example 1 are given. From Figure 4It can be seen that the electrochemically active surface area of Cu-PHMACⅡ is the highest, while that of Cu-PHMACⅠ is lower than that of pure copper powder. This is mainly because the addition of the copolymer reduces the conductivity of the catalyst. With the increase in the concentration of surface cations, the electrochemistry of the catalytic system increases. Therefore, Cu-PHMACⅡ has more surface active sites and higher electrochemistry activity. Figure 5 is the impedance diagram of the copper-based catalyst materials of Examples 1-2 and Comparative Example 1. From Figure 5 it can be seen that with the increase in the cation concentration, the impedance of the material also decreases more and more, which will help to improve the catalytic activity of the catalyst and increase the reaction rate.
[0068] Comparative Example 2
[0069] The difference between Comparative Example 2 and Example 1 is that the molar amount of N-(hydroxymethyl) acrylamide (HAM) is increased to 3 mmol. The finally prepared catalyst is Cu-PHMACⅢ.
[0070] Comparative Example 3
[0071] The difference between Comparative Example 3 and Example 1 is that step (2) is replaced with: the reaction mixture obtained in step (1) is degassed with argon at room temperature for 30 min. Under an argon atmosphere, the reaction mixture is stirred in an oil bath at 60 °C for 48 h. The polymer solution is precipitated in cold ether. The product is reprecipitated twice in methanol / ether and dried in vacuo to obtain a white solid (PHM). The finally prepared catalyst is Cu-PHM.
[0072] Comparative Example 4
[0073] The difference between Comparative Example 4 and Example 1 is that the amount of methyl methacrylate used is adjusted to 1 mmol.
[0074] Application Example 1
[0075] A method for electrocatalytic reduction of CO2 using a copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer, comprising the following steps:
[0076] (1) Preparation of the working electrode: Take Cu-PHMACⅠ, weigh 3 mg, place it in a sample bottle, add 1 mL of isopropanol and 100 μL of naphthol, ultrasonically disperse for 30 min, cut carbon paper of model 28BC into 1×1 cm -2 , and use an airbrush to spray the prepared solution onto the carbon paper, controlling the catalyst loading to be 1 mg cm -2 , and dry the sprayed carbon paper at room temperature for 8 h to completely volatilize the dispersant isopropanol.
[0077] (2) Setup of the flow cell device with a three - electrode system: Using a platinum sheet as the counter electrode, an Ag / AgCl as the reference electrode, a mixed solution of 0.1 mol / L sulfuric acid and 0.25 mol / L potassium sulfate as the anodic electrolyte, and the same solution as the cathodic electrolyte, set up the flow cell device with a three - electrode system;
[0078] (3) Electro - catalytic CO₂ reduction:
[0079] Perform electrochemical tests under constant current conditions and test the catalyst performance at current densities of 100, 200, 250, 300, 400 mA / cm 2 . After the reaction, use a Fuli GC9720 Plus thermal conductivity - gas chromatography to detect the gas products generated during the reaction, such as H₂, CH₄, CO, C₂H₄, etc. Among them, Cu - PHMACⅠ is prepared according to the method of Example 1.
[0080] The performance graph of the catalyst for carbon dioxide reduction (CO₂ER) in Application Example 1 is as Figure 6 shown. The FE of Cu - PHMACⅠ C2 reached 52% at a current density of 200 mA / cm 2 . Among them, FE C2H5OH = 36.1%. At this current density, FE H2 decreased to 16.4%, indicating that Cu - PHMACⅠ reduced the HER reaction during the CO₂ER process, and the CO intermediates enriched on the catalyst surface were more inclined to couple than to desorb.
[0081] Application Example 2
[0082] The difference between Application Example 2 and Application Example 1 is that Cu - PHMACⅡ is used instead of Cu - PHMACⅠ, where Cu - PHMACⅡ is prepared according to the method of Example 1.
[0083] The performance graph of the catalyst for carbon dioxide reduction (CO₂ER) in Application Example 2 is as Figure 7 shown. Its FE C2 reached 72.5% at a current density of 250 mA / cm 2 . Among them, FE C2H5OH = 46.6%. Compared with Cu - PHMACⅠ, the Faraday efficiency of C₂ products increased. At a current density of 250 mA / cm 2 , FE C2 increased by about 20%. This is because the increase in cation concentration forms a tight double - layer structure at the electrode / solution interface, changing the local electric field distribution and hydrogen ions (H +The mass transfer process of , meanwhile, the dehydrated cations are closer to the electrode surface, forming a dynamic coordination with CO intermediates, stabilizing the polarized transition state of C-C coupling, and significantly reducing the reaction energy barrier. The CO2 gas also better contacts the catalyst surface, so the Faraday efficiency of C2 products such as ethylene increases.
[0084] Application Example 3
[0085] The difference between Application Example 3 and Application Example 1 is that the commercial copper powder in Comparative Example 1 is used instead of Cu-PHMACⅠ.
[0086] The performance graph of the commercial copper powder catalyzing carbon dioxide reduction (CO2ER) is as Figure 8 shown, where FE H2 is about 30-40%, and the FE of the copper powder reaches 37% at 200 mA / cm 2 . However, the desorption of *CO on the copper powder is also relatively serious, so its FE C2 is 28% at 250 mA / cm 2 . It can be seen that the enrichment and rapid desorption of CO on its surface result in a relatively high Faraday efficiency of CO, and mainly C1 products are generated. CO
[0087] Application Example 4
[0088] The difference between Application Example 4 and Application Example 1 is that Cu-PHMACⅢ in Comparative Example 2 is used instead of Cu-PHMACⅠ.
[0089] The performance graph of the catalyst in Application Example 4 catalyzing carbon dioxide reduction (CO2ER) is as Figure 9 shown, where FE H2 is about 30%, and the total gas Faraday efficiency reaches about 50%. Compared with Cu-PHMACⅠ, Cu-PHMACⅢ is more conducive to the HER reaction in the CO2ER process, and its performance is similar to that of pure copper powder.
[0090] Application Example 5
[0091] The difference between Application Example 5 and Application Example 1 is that Cu-PHM in Comparative Example 3 is used instead of Cu-PHMACⅠ.
[0092] The performance graph of the catalyst in Application Example 5 catalyzing carbon dioxide reduction (CO2ER) is as Figure 10 shown, where FE H2 is about 40-50%, and the hydrogen evolution reaction is relatively serious. Cu-PHM increases the relative content of HAM, making it easier for H + to bind to the catalyst surface, resulting in an intensification of HER.
[0093] Application Example 6
[0094] The difference between Application Example 6 and Application Example 1 is that the catalyst in Comparative Example 4 is used instead of Cu-PHMACⅠ.
[0095] Electrochemical tests were carried out under constant current conditions, and the performance of the catalyst was tested at different current densities. Since the relative content of HAM was increased, but the content of OH - increased, resulting in the surface of the catalyst being more likely to combine with H + , and it was found that its performance was similar to that of pure copper powder.
[0096] Comparing Application Examples 1 to 6, it can be seen that the Cu-PHMACⅡ prepared in Application Example 2 has high selectivity for electrocatalytic production of C2 products, and its FE C2 reached 72.5% at a current density of 250 mA / cm², where FE C2H5OH = 46.6%. The catalyst prepared by the present invention is simple to synthesize and inexpensive, and can greatly save costs when applied to industrial production. It is a new type of catalytic material with great industrial electrocatalytic prospects.
[0097] The embodiments provided above are not intended to limit the scope covered by the present invention, nor are the described steps intended to limit the order of their execution. Obvious improvements made by those skilled in the art to the present invention in combination with the existing common general knowledge also fall within the protection scope defined by the claims of the present invention.
Claims
1. A preparation method of a quaternary ammonium cation cross-linked copolymer-coated copper-based catalyst, characterized in that, It includes the following steps: (1) Dissolve methyl methacrylate, a crosslinking agent and an initiator in methanol under an inert atmosphere to obtain a reaction mixture; (2) Dissolve a cationic polymerizable monomer in water, add the reaction mixture obtained in step (1) to the solution, heat and stir the mixture under the protection of an inert gas, and obtain a quaternary ammonium cation crosslinked copolymer after extraction, precipitation, washing and drying of the mixed solution; (3) Mix copper powder and the quaternary ammonium cation crosslinked copolymer obtained in step (2) evenly to obtain a mixture, add a solvent to the mixture to dissolve it, and obtain a copper-based catalyst coated with the quaternary ammonium cation crosslinked copolymer.
2. The preparation method according to claim 1, wherein The crosslinking agent described in step (1) includes any one of acrylamide, methacrylamide, N-methylmethacrylamide, N-isopropylmethylmethacrylamide, N,N-dimethylmethylmethacrylamide, N,N-diethylmethylmethacrylamide, N-methyl-N-ethylmethylmethacrylamide, N-hydroxyethylmethylmethacrylamide, N-(hydroxymethyl)acrylamide, dopamine methacrylamide, and the initiator includes at least one of 2,2'-azobis(2-methylpropionitrile), azobisisoheptanenitrile, dimethyl 2,2'-azobis(2-methylpropionate), azodicyanovaleric acid.
3. The preparation method according to claim 1, characterized in that, The cationic polymerizable monomer described in step (2) includes any one of methylacryloyloxyethyltrimethylammonium chloride, acryloyloxyethyltrimethylammonium chloride, acrylamidopropyltrimethylammonium chloride, diallyldimethylammonium chloride, [3-(methacrylamido)propyl]trimethylammonium chloride, and the molar ratio of the crosslinking agent, methyl methacrylate and the cationic polymerizable monomer is 1-1.3:2:1-2.
4. The preparation method according to claim 1, characterized in that, The molar ratio of the initiator and the crosslinking agent in step (1) is 10-20:1, the molar volume ratio of methyl methacrylate to methanol is 1 mmol:3-10 mL, and the inert atmosphere is argon or nitrogen.
5. The preparation method according to claim 1, characterized in that In step (2), the volume ratio of the water to the methanol in step (1) is 3-4:6-7. Before adding the reaction mixture, first purify the aqueous solution of the cationic polymerizable monomer. The solvents used for purification include at least one of ethyl acetate, cold ether and dichloromethane, and the volume ratio of the solvents used for purification to the aqueous solution of the cationic polymerizable monomer is 1:2-3.
6. The preparation method according to claim 1, wherein The inert gas in step (2) is argon or nitrogen, the heating temperature is 70-80 °C, the stirring time is 36-48 h, and the extraction and precipitation are to extract and precipitate the mixed solution with an organic solvent. The organic solvent includes at least one of cold ether, dichloromethane and ethyl acetate.
7. The preparation method according to claim 1, wherein In step (2), the extraction and precipitation are to first extract and precipitate it with cold ether, and then extract and precipitate it twice with dichloromethane. The drying is to dry it in a vacuum oven at 50-70 °C for 10-12 h.
8. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of the copper powder to the quaternary ammonium cation crosslinked copolymer is 3-5:1, the solvent is at least one of dichloromethane, methanol and ethyl acetate, and the mass volume ratio of the mixture to the solvent is 5-6 mg:1 mL.
9. A copper-based catalyst coated with a quaternary ammonium cation cross-linked copolymer prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the copper-based catalyst coated with the quaternary ammonium cation cross-linked copolymer according to claim 9 in the electrocatalytic reduction of CO2 to ethanol.